Multi-hazard Response and Fragility Modeling of Bridges with Shallow Foundations - Biazar, Sina (My University, 2023)
In Canada, bridges are susceptible to multiple hazards such as earthquake, scour, flood, vehicular loads, etc. Most riverine bridges, which are significantly more susceptible to scour, have deep foundations. Hence, while there are several studies targeting damage assessment of bridges under multi-hazard scenarios, Limited research has been conducted regarding shallow foundation bridges and their response has remained relatively unknown. This study aims at advancing the knowledge on multi-hazard damage assessment of shallow foundation bridges in Canada. The contributions of this study are: 1) To investigate the elemental and overall response of shallow foundation bridges on multi-hazard scenarios by conducting numerical analysis 2) To propose a probabilistic damage assessment framework for bridges with shallow foundations exposed to seismic, scour, and vehicular loadings to facilitate policy-making toward disaster planning and emergency response, 3) To determine which parameters will affect the overall seismic response of a scoured bridge under vehicular loading and to examine which bridge components might affect the damage state of the bridge, and 4) To investigate the probability of any positive scour effect on the seismic response of the bridge. To this end, an extensive literature review has been conducted on 3D structural modeling, soil modeling, and scour modeling. A verified finite-element model has been developed and analyzed by conducting several numerical analyses based on the literature and novel ideas. Finally, a framework has been created explaining how to develop fragility models for shallow foundation bridges. The framework is showcased using a typical bridge in eastern Canada. The results indicate that although scour notably increases the elemental and overall damage of typical shallow foundation bridges, while the scour depth is lower than the foundation height, the increased damage does not impose a significant threat on the bridge safety. In terms of importance, earthquake, scour, and then vehicular loads have the most effect on the bridge response.